Effect of Cyanophage Infection on CO(2) Photoassimilation in Plectonema boryanum - Ginzburg, Dalia (1968)
Cyanophage infection effects a rapid and complete cessation of CO(2) photoassimilation in Plectonema cells. From the amount of infected cells lysed, it was established that this phenomenon cannot be ascribed to lysis of the host cells either from within or from without. The possibility that the effect is due to nitrogen starvation, induced secondarily by cyanophage multiplication, was ruled out when it was found that nitrogen supplementation did not influence the inhibition. It is suggested that the arrest of CO(2) photoassimilation is an integral part of the cyanophage infection cycle in P. boryanum. This idea is supported by the nondependence of the cyanophage-induced inhibition on the input multiplicity, by the light requirement for the inhibition, and by the fact that infected Plectonema cells with inhibited CO(2) photo-assimilation support normal multiplication of the cyanophage. The pattern of light requirement for this viral inhibition further supports this suggestion.